2019
DOI: 10.1111/vsu.13306
|View full text |Cite
|
Sign up to set email alerts
|

Use of perioperative variables to determine the requirement for repeat celiotomy in horses with postoperative reflux after small intestinal surgery

Abstract: Objective To determine whether perioperative variables can be used to differentiate a medical vs a surgical reason for postoperative reflux (POR) after small intestinal (SI) surgery in horses. Study design Retrospective study. Sample population Horses >1 year of age that recovered from SI surgery and had POR. Methods Medical records of horses that underwent SI surgery and developed POR from 2009‐2015 were reviewed. Surgical reasons for POR were defined as an anastomosis complication, mechanical obstruction, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Freeman et al 16 found that a higher rectal temperature (>39.1°C) postoperatively after colic surgery was associated with an increased risk of Salmonella shedding. Another recent study 17 looking at horses with POR after small intestinal surgery found that horses that developed a fever or colic signs in the postoperative period were more likely to have a surgical reason for having POR. However, as part of that study horses positive for Salmonella were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Freeman et al 16 found that a higher rectal temperature (>39.1°C) postoperatively after colic surgery was associated with an increased risk of Salmonella shedding. Another recent study 17 looking at horses with POR after small intestinal surgery found that horses that developed a fever or colic signs in the postoperative period were more likely to have a surgical reason for having POR. However, as part of that study horses positive for Salmonella were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Post-anaesthetic ileus (POI) is a specific cause of PAC and is described in 6-40% of horses after abdominal surgery with varying mortality from 14 up to 66% (Mee et al 1998b;Freeman et al 2000;Morton and Blikslager 2002;Proudman et al 2002;Cohen et al 2004;Mair and Smith 2005a,b;Holcombe et al 2009;Torfs et al 2009Torfs et al , 2015Jacobs et al 2019). The diagnosis is based on small intestinal dysmotility and/or distension with reflux of large volumes of intestinal content, tachycardia, abdominal discomfort, reduced faecal output or absent borborygmy (Lefebvre et al 2016).…”
Section: Post-anaesthetic Ileusmentioning
confidence: 99%